2016
DOI: 10.18805/ijar.v0iof.4563
|View full text |Cite
|
Sign up to set email alerts
|

The effect of some pre-slaughter factors on meat quality of bulls slaughtered in a commercial abattoir in Turkey

Abstract: One-hundred and eighteen bulls slaughtered at Van city abattoir were evaluated to determine the effects of some pre-slaughter factors on meat quality traits. The effect of breed on meat quality traits was limited except for water holding capacity (WHC) and Brown Swiss cross bulls had higher WHC than Simmental cross bulls. Bulls aged 30 months and older had higher pH24h (6.05 vs. 5.76; p less than 0.001) and lower L* and b* values than younger bulls. Bulls that were transported from 300 km away had significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
0
1
0
1
Order By: Relevance
“…This effect was found to have been particularly intense when lairage time was insufficient for the animals to recover after long journeys [39,49]. Another study confirmed that bulls transported over long distances (300 km) produced meat with a significantly higher pH than bulls transported for only 125 km [50]. It was also concluded that animals transported over longer distances (850 km) exhibited higher exhaustion symptoms, increased blood glycogenolysis levels, and higher meat pH in comparison with animals transported over medium distances (450 km) [48].…”
Section: Transport Distance (Td)mentioning
confidence: 86%
“…This effect was found to have been particularly intense when lairage time was insufficient for the animals to recover after long journeys [39,49]. Another study confirmed that bulls transported over long distances (300 km) produced meat with a significantly higher pH than bulls transported for only 125 km [50]. It was also concluded that animals transported over longer distances (850 km) exhibited higher exhaustion symptoms, increased blood glycogenolysis levels, and higher meat pH in comparison with animals transported over medium distances (450 km) [48].…”
Section: Transport Distance (Td)mentioning
confidence: 86%
“…Posterior al período de espera en los corrales, los animales son trasladados a la sala de beneficio, en donde nuevamente son sometidos a factores estresantes como son nuevos olores, ruidos desconocidos y al uso de instrumentos para movilizarlos hasta la caja de aturdimiento (58). Por esta razón, el protocolo de beneficio y el nivel de tecnología utilizado en la planta pueden llegar a ser determinantes en la presentación de carne DFD (59).…”
Section: Factores Pre Y Post Beneficio Que Afectan La Presencia De Ca...unclassified